Marine Shipping Industry Within the System of Global Economic Relations Sustainability - Frasyniuk, Tatyana; Primachova, Natalia (International Journal of Engineering and Technology, 2018)
In the current article we study patterns and conditions, under which the role of marine shipping industry within the system of balanced sustainable development of mega economics can be increased. We concentrate attention on the synchronism of emerging problems of differentiation certain economical subsystems and issues of keeping the priorities of development and sustainable positioning. Marine shipping industry holds a special position within international economic relations. Being under the general market relations laws, it predetermines the parameters of supply segment in a limited way. That is why unbalanced cargo traffic and fleet freight capacity cause integral and external losses. Despite system dependence on the international trade pattern, commercial shipping is essential for innovative development of big maritime states' industrial sector.Â